1988
DOI: 10.1016/0198-0149(88)90032-5
|View full text |Cite
|
Sign up to set email alerts
|

The relative contributions of advection and isopycnal and diapycnal mixing below the subtropical salinity maximum

Abstract: Abstract--The spatial distribution of the subtropical salinity maximum is identified using historical and recent data from the eastern North Atlantic. In the regions with high frequency of occurrence of the salinity maximum, the relative contributions of advection, eddy diffusion and double diffusion to the salt balance below the maximum salinity layer are determined. McDoUGALL's (1984, Journal of Physical Oceanography, 14, 1577-1589 salt balance equation for neutral surfaces is used in this analysis. The data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

1991
1991
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 16 publications
0
21
0
Order By: Relevance
“…This corresponds to waters formed at the sea surface, in areas where evaporation exceeds precipitation, that sink due to Ekman transport and winter vertical convection. Throughout spring and summer there is surface capping of this salinity anomaly, which then spreads horizontally over long distances (Bauer and Siedler 1988).…”
Section: Spatial Distribution Of Water Propertiesmentioning
confidence: 99%
“…This corresponds to waters formed at the sea surface, in areas where evaporation exceeds precipitation, that sink due to Ekman transport and winter vertical convection. Throughout spring and summer there is surface capping of this salinity anomaly, which then spreads horizontally over long distances (Bauer and Siedler 1988).…”
Section: Spatial Distribution Of Water Propertiesmentioning
confidence: 99%
“…In the northwest, we recognize the typical subtropical Salinity Maximum Water of the North Atlantic. This water mass is formed in the inner subtropical gyre where evaporation exceeds precipitation, and has recently been studied hy BAUER and SIEDLER (1988).…”
Section: New Datamentioning
confidence: 99%
“…Recently, HAMILTON et al, (1989) suggested that salt fingers and associated double diffusion might be an important process in the vertical flux of nitrate. Diapycnal mixing due to salt fingering has been observed when warm and more saline water overlies cold and less saline water layers (BAUER and SIEDLER, 1988). Such a situation was given after intrusion of warm and saline Smax over cold and less saline Central Water during our drift study (PODEWSKI et al, 1993).…”
Section: Nitrate Supply To the Euphotic Zone In The Tropical Oceanmentioning
confidence: 97%
“…The depth of the Sma × layer is critical for the distribution of nitrate within ~ "potential euphotic zone" of 115-125 m. Usually, the core of the Smax water in the tropical North Atlantic is observed between 80 and 150 m (WORTHINOTON, 1976;BAUER and SIEDLER, 1988), however, it rises towards the Equatorial Counter Current, where it can bc found at 50 m depth (PETERS, 1978;BAUER and SIEDLER, 1988). WORTHINGTON (1976~ showed that the Smax water keeps its oxygen signature of about 100% saturation for a great distance from its formation at the surface.…”
Section: Nose-like Nitrate Profiles: a Unique Situation?mentioning
confidence: 99%
See 1 more Smart Citation